Validity And Reliability Of Digital Health Education On Diabetic Foot Care Based On Health Belief Model Among Type Ii Diabetic Patients - Widodo, Wahyu; Said, Faridah Mohd Said; Aljaberi, Abdulwahid (Enrichment: Journal of Multidisciplinary Research and Development, 2024)
The study aims to evaluate the effectiveness of digital health education on diabetic foot care among type II diabetic patients using the Health Belief Model (HBM). A total of 30 participants were recruited from local diabetes clinics to receive digital health education focused on diabetic foot care practices. To ensure the validity and reliability of the assessment tools, we employed multiple methods. Content validity was established through expert reviews, while construct validity was examined using Exploratory Factor Analysis (EFA) and Confirmatory Factor Analysis (CFA), which confirmed a good factor structure aligned with the HBM constructs. Reliability was assessed using Cronbach’s alpha for internal consistency, which showed acceptable values ranging from 0.67 to 0.84, and test-retest reliability with Intraclass Correlation Coefficients (ICC) ranging from 0.74 to 0.78. The results indicate that the digital health education program significantly improved the participants' understanding and practices related to diabetic foot care. These findings underscore the potential of digital education interventions for chronic disease management, particularly for enhancing self-care behaviors in diabetic patients. Future studies should consider larger sample sizes to further validate these tools and results. Overall, this study provides evidence supporting the effectiveness of digital health education for diabetic foot care and validates the reliability and validity of the instruments used.